2019
DOI: 10.1055/s-0037-1610676
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Catalyzed Regio- and Diastereoselective Synthesis of Spiroisoxazolines via One-Pot Sequential Knoevenagel Condensation/1,3-Dipolar Cycloaddition Reaction

Abstract: A ZnCl2-catalyzed regio- and diastereoselective one-pot sequential Knoevenagel condensation/1,3-dipolar cycloaddition reaction of CH acids (oxindole, 1,3-indandione, and 3H-pyrazol-3-one), aldehydes, and dibromoformaldoxime has been established. The method allows the synthesis of diversely functionalized spiroisoxazolines in good isolated yields under mild reaction conditions. Moreover, the preparation of spiroindene-isoxazole-1,3-diones containing benzoimidazole or benzothiazole moieties as new ligands for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…ZnCl 2 was used as the Lewis acid-based catalyst and bromonitrile oxide 377 as the main reactant. Starting from indane-1,3-dione 4, aromatic aldehydes 368 and dibromonitrile oxide 377 in basic conditions in THF at 45 • C, spiro-compounds comprising an isoxazole moiety 378 could be obtained (see Table 23 and Scheme 107) [289]. Lewis acids were also used to synthesize spiro compounds by domino reactions, and the combination of a Knoevenagel condensation and a 1,3-dipolar cycloaddition was notably examined.…”
Section: Synthesis Of Spiro-indane-13-diones By Domino Reactionmentioning
confidence: 99%
“…ZnCl 2 was used as the Lewis acid-based catalyst and bromonitrile oxide 377 as the main reactant. Starting from indane-1,3-dione 4, aromatic aldehydes 368 and dibromonitrile oxide 377 in basic conditions in THF at 45 • C, spiro-compounds comprising an isoxazole moiety 378 could be obtained (see Table 23 and Scheme 107) [289]. Lewis acids were also used to synthesize spiro compounds by domino reactions, and the combination of a Knoevenagel condensation and a 1,3-dipolar cycloaddition was notably examined.…”
Section: Synthesis Of Spiro-indane-13-diones By Domino Reactionmentioning
confidence: 99%
“…It was begun by the propargylation of pentaerythritol using propargyl bromide with potassium hydroxide in dry DMF (Scheme 1) [32], followed by the 1,3dipolar cycloaddition on the tetrapropargylated core (3) using a bromonitrile oxide precursor (4) in THF at 45 °C for 3 h, with NaHCO3 as base and ZnCl2 as a catalyst. It afforded 5,5′-(((2,2-bis(((3bromoisoxazol-5-yl)methoxy)methyl)propane-1,3-diyl)bis(oxy))bis(methylene))bis(3bromoisoxazole) (5) in 44% isolated yield (Scheme 1) [33]. A tremendous research effort has been devoted to developing nanocarriers that could deliver active pharmaceutical agents to the sites affected by pathological changes to minimize wide body distribution and reduce undesirable side effects [20,21].…”
Section: Synthesismentioning
confidence: 99%
“…It was begun by the propargylation of pentaerythritol using propargyl bromide with potassium hydroxide in dry DMF (Scheme 1) [32], followed by the 1,3-dipolar cycloaddition on the tetrapropargylated core (3) using a bromonitrile oxide precursor (4) in THF at 45 • C for 3 h, with NaHCO 3 as base and ZnCl 2 as a catalyst. It afforded 5,5 -(((2,2-bis(((3-bromoisoxazol-5-yl)methoxy)methyl)propane-1,3-diyl)bis(oxy))bis(methylene))bis(3-bromoisoxazole) (5) in 44% isolated yield (Scheme 1) [33].…”
Section: Synthesismentioning
confidence: 99%
“…And many elegant building blocks have been devised to achieve this goal, including 1-indanone and its derivatives, [6][7][8] 1,3-indanedione and its derivatives, 9,10 and others. [11][12][13][14][15][16][17][18][19] As sterling building blocks for the construction of polycyclic indene frameworks, indenedienes have aroused great interest of synthetic chemists due to their unique structural features in the synthesis of polycyclic indene scaffolds, 20 and they could serve not only as four-atom reaction partners in (4 + n) annulation for constructing indene-fused cyclic scaffolds, but also as two-atom reaction partners in (2 + n) annulation for constructing spiroindene scaffolds (Scheme 1b). Recently, our group has been interested in exploiting the reactivities of indene-dienes.…”
mentioning
confidence: 99%
“…With the amount ratio of 1 : 2, a 79% isolated yield of 3a could be obtained (entry 8). Afterward, several representative solvents were evaluated (entries [9][10][11][12][13][14][15][16][17]. The results demonstrated that the solvents had an apparent influence on the yields and 1,2dichloroethane was the best choice for this (4 + 2) cyclization (entry 13).…”
mentioning
confidence: 99%